Root Canal Dentin Microhardness after Contact with Antibiotic Medications: An In Vitro Study - Amanda Palmeira Arruda Nogueira; Renata Grazziotin-Soares; Adriana Marques Mesquita Leal; Sérgio Alves Guida Freitas Júnior; Bruna Laís Lins Gonçalves; José Bauer; Meire Coelho Ferreira; Ceci Nunes Carvalho (MDPI AG, 2024)
Background: Antibiotic pastes used as intracanal medication in cases of revascularization therapy might cause negative effects on tooth properties, such as a reduction in dentin microhardness. This in vitro study investigated dentin microhardness in three different locations distancing from the canal lumen after 20 days of treatment with a tri-antibiotic paste (ciprofloxacin, metronidazole, and minocycline), and with a double-antibiotic paste (ciprofloxacin and metronidazole), with calcium hydroxide [Ca(OH)2] UltracalTM XS-treated dentin as comparison. Material and Methods: Human mandibular premolars (n = 48) had the root canals cleaned and shaped and were used to produce dentin slices. Dentin slices remained immersed in the medications for 20 days. The Knoop microhardness (KHN) test was performed before (baseline/Day-0) and after treatment (Day-20) with the medications. Indentations were made at 25 µm, 50 µm, and 100 µm distances from the root canal lumen. The KHN was compared intra-group using Wilcoxon's test. Independent groups were compared using Mann-Whitney's and Kruskal-Wallis' tests, at α = 5%. Results: The microhardness in all the tested groups was reduced at Day-20 in comparison with Day-0 (p < 0.001) (intra-group comparison/same distances). The Day-0 values were similar, and the Day-20 values were higher for the Ca(OH)2 group (p < 0.05) (comparison between groups/same distances). Conclusions: Calcium hydroxide for 20 days would be preferred rather than antibiotic pastes to minimize the expected reduction in dentin microhardness during regenerative procedures.